No Histological Difference between Large Atherosclerotic and Cardiogenic Embolic Thrombus. (4th March 2022) - Chen, Rui; Zeng, Xiaopeng; Liu, Yong; Huang, Cheng; Yang, Jun
Abstract : Background . The continuous development of endovascular treatment technology provides more opportunities for the histological study of thrombus. According to Trial of Org 10 172 in Acute Stroke Treatment (TOAST), clinicians take different strategies in anticoagulant or antiplatelet therapy. There are some patients still suffering from recurrent stroke while they took anticoagulant or antiplatelet drugs regularly for secondary prevention. In view of that, we found that histological analysis of thrombus can provide guidance for secondary prevention. Aim . Exploring the histological characteristics differences between large atherosclerotic and cardiogenic embolic thrombosis in order to guide clinical secondary prevention of the two stroke subtypes. Methods . A total of 54 patients with acute ischemic stroke were collected from December 2019 to April 2021. Identify stroke subtypes according to TOAST classification. Stain thrombus specimens with hematoxylin-eosin staining, and perform statistical analysis on the components (red blood cells and fibrin/platelets) of thrombus. Results . In cardiogenic thrombi, the composition of RBCs was dominant (51.38 ± 18.463 %) compared to that of fibrin/platelets (48.62 ± 18.463 %). Similarly, among the thrombi of large artery atherosclerotic, RBCs (50.40 ± 20.100 %) compared to fibrin/platelets (49.60 ± 20.100 %). There was no statistical difference in RBCs or fibrin/platelet composition of both cardiogenic and atherosclerotic thrombi (P = 0.89 ). Conclusions . The histologic composition of thrombi in cardiogenic and atherosclerotic had no statistical difference. These thrombi are all mixed thrombus, which are rich in RBCs, fibrinogen, and platelets. Anticoagulation combined with antiplatelet may be a more effective secondary prevention strategy.